Single Crystals Based on Hydrogen-Bonding Mediated Cation–Anion Assembly with Extremely Large Optical Nonlinearity and Their Application for Intense THz Wave Generation - Lee, Seung Chul; Kang, Bong Joo; Lee, Ji Ah; Lee, Seung Heon; Jazbinšek, Mojca; Yoon, Woojin; Yun, Hoseop; Rotermund, Fabian; Kwon, O. Pil (Advanced Optical Materials, 2018)
New molecular salt crystals based on linear-shaped polymer-like cation–anion assembly exhibiting extremely large nonlinear optical response and high THz generation efficiency are reported. Two hydroxy benzothialzolium PMB (2-(4-(4-(hydroxymethyl)piperidin-1-yl)styryl)-3-methylbenzo[d]thiazol-3-ium) crystals with different benzenesulfonate counter anions provide isomorphic crystal structure with acentric monoclinic Cc space group symmetry. In contrast to previously reported benchmark nonlinear optical salt crystals with a parallel-type cation–anion assembly, newly developed PMB-based crystals exhibit a series-type cation–anion assembly mediated by strong bidentate-like hydrogen-bonds. Such series-type cation–anion assembly results in perfect alignment of highly nonlinear PMB cations in the crystalline state, leading to extremely large diagonal component of the second-order nonlinear optical coefficient exceeding that of the state-of-the-art nonlinear optical crystals. In THz wave generation experiments based on optical rectification, a 0.33 mm thick PMB crystal generates intense THz pulses with peak-to-peak THz electric field of 430 kV cm−1 and extremely broad flat spectrum with upper cut-off frequency of above 8.0 THz. In addition, compared to inorganic standard 1.0 mm thick ZnTe crystals, the PMB crystal delivers a 24 times higher THz electric field and about 3 times broader bandwidth. Therefore, hydroxy benzothialzolium PMB crystals are highly desired novel materials for various nonlinear optical applications including THz photonics.
Keywords: Large optical nonlinearities; Nonlinear optical applications; Nonlinear optical crystal; Nonlinear optical response; Optical rectifications; Organic crystal; Second-order nonlinear optical coefficient; Space-group symmetry; nonlinear optics; organic crystals; terahertz waves